Le Rôle conservatoire des magistrats collectionneurs sous l’Ancien Régime : l’exemple de la collection Le Nain / de Cotte de l’Assemblée nationale - Sarah de Bogui (In Situ)
Through the example of the Le Nain / de Cotte collection kept in the library of the French National Assembly, we will demonstrate how, thanks to the permeability between institutional archives and private archives, the passion for collecting of two magistrates has enabled to preserve and make accessible the holdings built up between 1250 and 1790, in the Parliament of Paris. Therefore, we will particularly focus on these men’s lives and on their collections.This example will be the opportunity to discuss the conditions for the movement of the records of the Parliament in the context of the professional practices of judicial officers in the 17th and 18th centuries. We will see how these practices, conditioned at the same time by the way in which justice was exercised, but also by resource constraints, working habits and the birth of bibliophilia, have contributed to the preservation of the records through dissemination.Finally, we will take a closer look at an exceptional judicial archival item with a mysterious trajectory that belongs to this collection: one of the original drawing-up of Joan of Arc’s trial. This copy raises, indeed, several questions on which it will be possible to formulate a few hypotheses since we are faced, in this case, with a document whose circulation trajectory, from the 15th century to the end of the Ancien Regime, is closely linked to the use of its probative value.